Landscape and culture cross-linguistic perspectives - Bromhead, Helen, 1981- (Cognitive linguistic studies in cultural contexts ;, 2018)
"The relationship between landscape and culture seen through language is an exciting and increasingly explored area. This ground-breaking book contributes to the linguistic examination of both cross-cultural variation and unifying elements in geographical categorization. The study focuses on the contrastive lexical semantics of certain landscape words in a number of languages. The aim is to show how geographical vocabulary sheds light on the culturally - and historically - shaped ways people see and think about the land around them. Notably, the study presents landscape concepts as anchored in a human-centred perspective, based on our cognition, vision, and experience in places. The Natural Semantic Metalanguage (NSM) approach allows an analysis of meaning which is both fine-grained and transparent. The book is aimed, first of all, at scholars and students of linguistics. Yet it will also be of interest to researchers in geography, environmental studies, anthropology, cultural studies, Australian Studies, and Australian Aboriginal Studies because of the book's cultural take"--